Incidence and risk factors for injuries in girls' high school volleyball: a study of 2072 players - McGuine, T. A.; Post, E.; Biese, K.; Kliethermes, S.; Bell, D.; Watson, A. M.; Brooks, A.; Lang, P. J. (Journal of Athletic Training, 2023)
Context Girls' high school volleyball is very popular across the United States. Prospective data are limited regarding the incidence and risk factors of time-loss (TL) and non-time-loss (NTL) injuries sustained in this population.